Pengaruh Model Pembelajaran Learning Cycle dan Penalaran Formal terhadap Hasil Belajar Matematika - Indra Puluhulawa; Evi Hulukati; Ali Kaku (Department of Mathematics, Universitas Negeri Gorontalo, 2020)
This article discusses the effect of the Learning Cycle model on mathematics learning outcomes in terms of formal reasoning. The study was conducted in the form of experiments involving students of SMP Negeri 1 Tibawa, Gorontalo. Data on mathematics learning outcomes and formal reasoning are obtained using multiple-choice tests that meet the item validity and instrument reliability requirements. Data analysis used a two-way analysis of variance and the Tuckey Test. Hypothesis testing is performed at a significant level of 0.05. The results showed that the learning outcomes of students who were taught using the Learning Cycle model were higher than the learning outcomes of students who were taught using the direct learning model in terms of formal reasoning. This result is strengthened by the existence of a significant interaction between learning models and formal reasoning towards mathematics learning outcomes. Student learning outcomes with high formal reasoning levels, get better learning outcomes in learning with the Learning Cycle model compared to students with low formal reasoning levels.